Probing Factors Influencing Students’ Bank Selection: A Case Study of British Gurkha College - Gole, Sonam (Nepal Journal of Multidisciplinary Research, 2023)
This study addressed the factors impacting students' bank choices in Nepal, bridging a research gap regarding Nepalese students. Employing a descriptive research design with quantitative methods, data was collected from 40 students. The findings unveiled influential factors: past bank experiences, bank image, staff friendliness, recommendations, interest rates, ATM services, mobile banking ease, debit card ease, direct bank approaches, advertising, bank location, and virtual access. These factors exhibited varying degrees of impact, with recommendations, bank location, and ATM services as prominent influencers. This study offers valuable insights for Nepal's banks to tailor marketing strategies and enhance their competitiveness in a burgeoning banking market.